Muse - Cavallaro, Brittany (Katherine Tegen Books, 2022)
Inventor Jeremiah Emerson is planning on unveiling a weapon that will showcase the power of his province, St. Cloud, to the rest of the First American Kingdom at the World's Fair. He has kept his daughter Claire under his control as he believes her touch grants him his genius. But when the weapon fails on opening day, Claire is kidnapped by St. Cloud's governor Remy Duchamp. With rival governorships jockeying for power, Claire realizes she may be the only person who can allow Remy is retain power. Soon, she must decide if she is going to remake her world or tear it down.